Analysis Of Factors Affecting Understanding Of MSMEs In The Preparation Of Financial Statements Based On SAK-EMKM On MSMEs In Banyumas District: Analisis Faktor-Faktor yang Mempengaruhi Pemahaman Pelaku UMKM dalam Penyusunan Laporan Keuangan Berdasarkan SAK-EMKM di Kecamatan Banyumas - Octisari, Sully Kemala; Indria Astuti , Yuniar Dwi; Adi Nugraha, Ginanjar (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine and analyze the effect of providing information and socialization, level of education, age of business, and business size on the understanding of SMEs in preparing financial reports based on SAK-EMKM, because MSME actors in Banyumas District have not carried out financial bookkeeping according to SAK-EMKM. This type of research uses quantitative research. There are 2 ways to collect data in this research, a questionnaire study and a literature study. Respondents in this study were Micro Business actors in Banyumas District. This study uses purposive sampling technique as a sampling method. The population of this study found 70 micro businesses and the sample in this study found 67 micro businesses. The analytical technique used in this study is multiple linear regression analysis with the help of SPSS software. The results in this study indicate that the simultaneous provision of information and socialization, education level, business age, and business size have a significant positive effect on the understanding of SMEs in preparing financial reports based on SAK-EMKM. Based on the partial study, it showed that the provision of information and socialization as well as the age of the business had a significant positive effect, while the level of education and business size did not have a significant positive effect on the understanding of MSMEs in compiling financial reports based on SAK-EMKM. The implication of the research results is to present training modules and practices that are carried out for MSME entrepreneurs.